Aprendizagem e desenvolvimento das funções mentais superiores das crianças com o transtorno do espectro autista - Cunha, Ane Cristine Herminio (2023)
Throughout the years policies and educational practices have been aligned to challenge the exclusion of vulnerable groups. Among them is the group of autistic people, aim of this research. This thesis analyzes the learning process and development of higher mental functions in 2 (two) autistic children and their inclusion in two regular classrooms of schools located in Cajazeiras/PB. We proposed the intervention in two schools to carry out this work, which is guided by culture-historical principles, and based on Vygotsky works as the main theoretical source. The connection of the work with the matrix demarcates the interweaving among the historical, cultural, social and semiotic dimensions when thinking about the subject. This work is classified as an applied, qualitative, historical-cultural approach, descriptive-analytical and intervention research. To reflect on the processes experienced in the schools, we also used the Microgenetics approach linked to the culture-historical matrix, with a special look at the intersubjective functioning. The intervention took place on December, 2021 and February, March. April and May, 2022, with an overall of 150 meetings from the initial data collection to the final action. In the beginning the children had difficulties in several mental functions, such as: attention, concentration, mental planning, language, interplay and perception. After the intervention we concluded that playful activities impacted the learning and development of autistic children in a positive way; the children developed mental functions, such as: attention, planning, language, among others; social participation and interaction has increased; the reduction of some symptoms, which have always been associated with autism, such as: stereotypies, isolation, withdrawal, touch aversion and robot-like speech; teachers became closer to these students; classroom planning was more suitable for pedagogical needs. Our work indicates that collaborative actions between university and school may produce pedagogically effective spaces, which promote social participation and interaction of students with special needs, their peers and teachers, contributing to the building of an inclusive society.________________________________________________________________________________________________________________________________